2020
DOI: 10.1039/d0ra08491c
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput morphology mapping of self-assembling ternary polymer blends

Abstract: Compositionally graded electrospray deposition combined with grazing incidence small angle X-ray scattering forms a high-throughput approach for mapping phase behavior in ternary mixtures as demonstrated here using block copolymer blends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…Similar expansions in interdomain distance as a function of chain length have been found in lamellae, cylinders, and spheres. ,,, The Hashimoto group worked on phase behavior in mixtures of polystyrene- b -polyisoprene (PS- b -PI) and hPS of various molecular weights. , Their studies demonstrated that as short-chain hPS is selectively incorporated into the PS block, uniform distribution of short hPS chains is preferred. Consequently, there is a high probability for chemical junctions between two the constituent PS and PI blocks to be swollen by short hPS chains so that area per block chain at the swollen chemical junction can increase.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Similar expansions in interdomain distance as a function of chain length have been found in lamellae, cylinders, and spheres. ,,, The Hashimoto group worked on phase behavior in mixtures of polystyrene- b -polyisoprene (PS- b -PI) and hPS of various molecular weights. , Their studies demonstrated that as short-chain hPS is selectively incorporated into the PS block, uniform distribution of short hPS chains is preferred. Consequently, there is a high probability for chemical junctions between two the constituent PS and PI blocks to be swollen by short hPS chains so that area per block chain at the swollen chemical junction can increase.…”
Section: Resultsmentioning
confidence: 70%
“…The level of complexity for BCP self-assembly in thin films and bulk can be increased by blending a homopolymer. The increased complexity is due to an interplay between spatial distributions of homopolymer chains in a BCP-based blend and the miscibility of homopolymer chains with constituent blocks of a BCP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ESD and GISAXS were used in a way analogous to what has been described in our previous work to systematically survey the combined effects of film thickness and composition. The basis for this survey is schematically depicted in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Systematic sample preparation and analysis are made possible using electrospray deposition (ESD) , to produce samples with different film thicknesses, all having gradients in composition from pure BCP to pure HP (at 1:1 PS:PMMA mass fractions). These samples are subsequently characterized using grazing-incidence small-angle X-ray scattering (GISAXS), through which domain spacing can be extracted as a function of film thickness and composition. Analysis of these data demonstrates unequivocally that HP can increase or decrease the domain spacing in BCP-HP blends depending on the HP molar mass.…”
Section: Introductionmentioning
confidence: 99%